2019
DOI: 10.1093/ajcn/nqz178
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intakes of flavan-3-ols and cardiometabolic health: systematic review and meta-analysis of randomized trials and prospective cohort studies

Abstract: Background Although available data suggest that some dietary flavan-3-ol sources reduce cardiometabolic risk, to our knowledge no review has systematically synthesized their specific contribution. Objective We aimed to examine, for the first time, if there is consistent evidence that higher flavan-3-ol intake, irrespective of dietary source, reduces cardiometabolic risk. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 57 publications
1
58
0
1
Order By: Relevance
“…Cardiovascular disease (CVD) is the leading cause of deaths worldwide. A number of recent meta-analyses of prospective cohort studies have indicated that individuals with the highest flavonoid intakes have lower relative risk of mortality from CVD and all-causes compared with that of individuals with the lowest intakes [111][112][113]. Several studies evidenced the beneficial effects of Allium flavonols on the cardiovascular system via their regulatory effects on platelet aggregation [83,84,96], atherogenesis [78], thrombotic activities [79], endothelial function [81], hypertension [77,82], lipid metabolism [77], and oxidative stress [42] (Table 3).…”
Section: Cardio-protective Effectsmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is the leading cause of deaths worldwide. A number of recent meta-analyses of prospective cohort studies have indicated that individuals with the highest flavonoid intakes have lower relative risk of mortality from CVD and all-causes compared with that of individuals with the lowest intakes [111][112][113]. Several studies evidenced the beneficial effects of Allium flavonols on the cardiovascular system via their regulatory effects on platelet aggregation [83,84,96], atherogenesis [78], thrombotic activities [79], endothelial function [81], hypertension [77,82], lipid metabolism [77], and oxidative stress [42] (Table 3).…”
Section: Cardio-protective Effectsmentioning
confidence: 99%
“…Indeed, it has been demonstrated that flavonoids, i.e., suppress the expression of pro-inflammatory mediators (NF-κβ cascade), have vasodilator activity, improve vascular endothelial function, protect cells against insulin resistance, regulate proliferation, and suppress neuroinflammation by reducing cytokine release [19][20][21][22][23][24][25][26]. As shown in many studies, the consumption of flavonoid-rich foods significantly decreases the possibility of cardiovascular disease development [11,[27][28][29]. A recent meta-analysis demonstrated that dietary intake of anthocyanins reduced the risk of coronary heart disease and cardiovascular disease mortality [30].…”
Section: Introductionmentioning
confidence: 99%
“…Four [ 35 , 36 , 37 , 38 ] and one [ 39 ] SRMA found that high intake of magnesium and flavonoid significantly decreased the risk of T2DM with pooled RRs ranging from 0.77 (95% CI: 0.72, 0.84) to 0.83 (95% CI: 0.80, 0.86) for high intake and pooled RR of 0.89 (95% CI: 0.82, 0.96) for dose response analysis ( Figure 3 A,B). However, one SRMA that assessed the effect of flavan-3-osl, a subclass of dietary flavonoid did not find the significant benefit of this subclass for the prevention of T2DM [ 40 ]. According to n-3PUFA, results from all three SRMAs did not show the significant benefit of a high intake of n-3 PUFA in prevention of T2DM [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Mediterranean (n = 4) and DASH diet showed protective effects on T2DM with the pooled RRs ranging from 0.77 (95% CI: 0.66, 0.89) [47] analysis ( Figure 3A,B). However, one SRMA that assessed the effect of flavan-3-osl, a subclass of dietary flavonoid did not find the significant benefit of this subclass for the prevention of T2DM [40]. According to n-3PUFA, results from all three SRMAs did not show the significant benefit of a high intake of n-3 PUFA in prevention of T2DM [41][42][43].…”
Section: Dietary Patternsmentioning
confidence: 93%